SLR PRISMA: Information Security's Role in Banking Data Integrity - Melati, Novian Tika; Ekasari, Kurnia; Susilowati, Kartika Dewi Sri (Journal of Applied Business, Taxation and Economics Research, 2025)
This study aims to explore the role of information security in maintaining banking data integrity in the digital era through a Systematic Literature Review (SLR) guided by the PRISMA protocol. A total of 55 relevant journal articles were analyzed using VOSviewer for bibliometric analysis and Taguette for thematic synthesis. The co-occurrence analysis revealed frequently used keywords such as internet banking, information security, technology, electronic banking, and customers, indicating a strong research focus on digital banking systems. Meanwhile, the co-authorship analysis showed limited collaboration among scholars, suggesting that the topic of information system security in the banking sector remains relatively underexplored. The thematic analysis identified key areas of concern, including the implementation of firewalls and intrusion detection systems, the development of secure integration models using OAuth 2.0, cryptographic measures such as AES-256 encryption, tokenization, and the Vigenère cipher, as well as the adoption of cloud computing and blockchain technology. Various cyber threats were also discussed, including data theft, transaction manipulation, credential misuse, malware, phishing, insider threats, and ransomware attacks. Furthermore, the importance of customer data protection was emphasized, particularly in relation to the Consumer Protection Law (UUPK). The findings underscore the need for enhanced technological solutions and stronger research collaboration to strengthen data integrity and security in the banking industry amid growing digital challenges.